Biomass, Biorefineries and Bioeconomy 2022
DOI: 10.5772/intechopen.102850
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion Pretreatment: Biomass Waste Utilization for Methane Production

Abstract: Lignocellulosic biomass as a second-generation biofuel resource such as waste from agricultural, forester industry, and unutilized wood and non-wood biomass was widely reported to use it as feedstock for methane production. As the carbon-neutral resources, biomass waste conversion for biofuel is in line with the SDGs 7 and 15 goal that can meet the needs and qualify to the standard of sustainable consumption and production pattern, and increasing the renewable energy. The wood and non-wood unutilized biomass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 121 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…It was found that phenolic hydroxyl (-OH) groups are responsible for lignin's antioxidant, antiultraviolet (UV) and antibacterial activities. [16][17][18] Antibacterial activity of natural compounds or molecules is of great interest nowadays due to the rise in AMR and the urge to develop novel drugs or treatments for various diseases. 19,20 Lignin derived from different plant sources has demonstrated a range of good antibacterial and antifungal activities against common microbes and human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that phenolic hydroxyl (-OH) groups are responsible for lignin's antioxidant, antiultraviolet (UV) and antibacterial activities. [16][17][18] Antibacterial activity of natural compounds or molecules is of great interest nowadays due to the rise in AMR and the urge to develop novel drugs or treatments for various diseases. 19,20 Lignin derived from different plant sources has demonstrated a range of good antibacterial and antifungal activities against common microbes and human pathogens.…”
Section: Introductionmentioning
confidence: 99%